Knowledge and experience of a cohort of HIV-positive and HIV-negative Ghanaian women after undergoing human papillomavirus and cervical cancer screening - Arabella Stuart; Dorcas Obiri-Yeboah; Yaw Adu-Sarkodie; Anna Hayfron-Benjamin; Angela D. Akorsu; Philippe Mayaud (BMC, 2019)
Abstract Background Cervical cancer is the most common cancer in women in Ghana, but knowledge and experience of women who have had cervical screening is under-evaluated. This study examined knowledge and understanding of HPV and cervical cancer and evaluated experiences of screening in a cohort of women of mixed HIV status. Methods This was a mixed methods study using questionnaires and focus group discussions, with a knowledge score constructed from the questionnaire. HIV-positive and HIV-negative women were recruited from a larger cervical screening study in Ghana and were interviewed 6 months after receiving screening. Quantitative data was analyzed and triangulated with qualitative data following thematic analysis using the framework approach. Results A total of 131 women were included (HIV-positive, n = 60). Over 80% of participants had a knowledge score deemed adequate. There was no difference between HIV-status groups in overall knowledge scores (p = 0.1), but variation was seen in individual knowledge items. HIV-positive women were more likely to correctly identify HPV as being sexually-transmitted (p = 0.05), and HIV negative women to correctly identify the stages in developing cervical cancer (p = < 0.0001). HIV-positive women mostly described acquisition of HPV in stigmatising terms. The early asymptomatic phase of cervical cancer made it difficult for women to define "what" cancer was versus "what" HPV infection was. All women expressed that they found it difficult waiting for their screening results but that receiving information and counselling from health workers alleviated anxiety. Conclusions Knowledge of women who had participated in a cervical screening study was good, but specific misconceptions existed. HIV-positive women had similar levels of knowledge to HIV-negative, but different misconceptions. Women expressed generally positive views about screening, but did experience distress. A standardized education tool explaining cervical screening and relevance specifically of HPV-DNA results in Ghana should be developed, taking into consideration the different needs of HIV-positive women.